Harga yang Harus Dibayar: Fenomena Beauty Penalty pada Mahasiswa Kota Banjarmasin - Zhafirah, Haura; Damaiyanti, Varinia Pura (Prodi Sosiologi FISIP ULM, 2025)
The phenomenon of beauty privilege refers to the social advantages gained by individuals considered physically attractive, yet it simultaneously imposes burdens and vulnerabilities, particularly on women labeled as “beautiful.” This study aims to explore the paradox of beauty privilege among female university students in Banjarmasin and to identify the forms of social pressure they experience in the process of social interaction. Using a qualitative method with a phenomenological approach, data were collected through observation, semi-structured interviews, and documentation. The findings reveal that beauty not only brings benefits but also entails consequences that create social burdens for women. Several participants reported experiencing competition among peers, expressed either openly or subtly through baseless remarks and even social exclusion. Women perceived as attractive are often attached to negative stereotypes, associating beauty with arrogance, lack of intelligence, or reliance solely on appearance. Furthermore, attractive women are also more vulnerable to subtle forms of violence disguised in less direct ways. This research provides insights into the paradox faced by women regarding beauty and the social pressures resulting from societal expectations of their appearance. Further research may explore how beauty bias operates in digital spaces, particularly the role of social media in creating constant surveillance of women’s bodies and lifestyles.